2009
DOI: 10.1002/aic.12093
|View full text |Cite
|
Sign up to set email alerts
|

Syngas chemical looping gasification process: Bench‐scale studies and reactor simulations

Abstract: in Wiley InterScience (www.interscience.wiley.com).The syngas chemical looping process co-produces hydrogen and electricity from syngas through the cyclic reduction and regeneration of an iron oxide based oxygen carrier. In this article, the reducer, which reduces the oxygen carrier with syngas, is investigated through thermodynamic analysis, experiments, and ASPEN Plus V R simulation. The thermodynamic analysis indicates that the countercurrent moving-bed reducer offers better gas and solids conversions when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
132
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 24 publications
5
132
0
Order By: Relevance
“…Syngas combustion in a moving bed reactor system was investigated by Fe-based oxygen carrier with 99.5% of syngas (44% CO and 29% H 2 ) conversion was achieved, which is closed to the values simulated by ASPEN PLUS . Degree of conversion with regards to Fe-based oxygen carriers by moving bed operation was approximately 50% that much greater than by fluidized bed operation with around 10% under the same condition (Li et al, 2010a). Thus, moving bed reactors with Fe-based oxygen carrier could be designed for smaller size, comparing to the fluidized bed reactors with similar heat capacity .…”
Section: Methane Reforming Reaction: Ch 4 + H 2 O ↔ Co + 3h 2 (7)mentioning
confidence: 99%
See 1 more Smart Citation
“…Syngas combustion in a moving bed reactor system was investigated by Fe-based oxygen carrier with 99.5% of syngas (44% CO and 29% H 2 ) conversion was achieved, which is closed to the values simulated by ASPEN PLUS . Degree of conversion with regards to Fe-based oxygen carriers by moving bed operation was approximately 50% that much greater than by fluidized bed operation with around 10% under the same condition (Li et al, 2010a). Thus, moving bed reactors with Fe-based oxygen carrier could be designed for smaller size, comparing to the fluidized bed reactors with similar heat capacity .…”
Section: Methane Reforming Reaction: Ch 4 + H 2 O ↔ Co + 3h 2 (7)mentioning
confidence: 99%
“…4 that are composed of a fuel reactor, a hydrogen generator, an air reactor (riser) and loop seals/valves, an air compressor and a cold trap (Sridhar et al, 2012). The moving bed chemical looping system was designed for application of Fe-based oxygen carriers moved counter-currently with fuels according to the thermodynamic analysis (Gupta et al, 2007;Li et al, 2010a). The crystalline phase distribution of Fe-based oxygen carriers are Fe 2 O 3 , Fe 3 O 4 , FeO and Fe from the top to the bottom in the counter-flow moving bed fuel reactor.…”
Section: Reactor Systems Of Chemical Looping Processmentioning
confidence: 99%
“…For the steam half cycle, the reduced oxygen carrier was oxidised into Fe3O4 producing a stream of 99.8 % pure hydrogen. In a separate study, the same group also demonstrated the feasibility of using a moving bed reactor at 900 °C for the same reaction [10]. A syngas conversion in excess of 99.5% and an oxygen carrier conversion of 50 % were recorded.…”
Section: Common Feedstocks For Producing Hydrogenmentioning
confidence: 91%
“…A number of studies have employed non-gaseous fuels including coal [8][9][10][11][12][13], biomass [14][15][16][17] and pyrolysis oil [18,19]. In a syngas chemical looping (SCL) process, the fuel is first converted into syngas in a separate gasification unit.…”
Section: Common Feedstocks For Producing Hydrogenmentioning
confidence: 99%
“…The combustion of syngas was noticeable for experiment conducted at 400°C, and reached 100% for experiments conducted at temperatures higher than 500°C. Based on the thermodynamic analysis by previous researchers (Wang et al, 2008;Li et al, 2010), CO and H 2 can be completely converted to CO 2 and H 2 O through the exothermic reaction with Fe 2 O 3 (or Fe 2 TiO 5 ) at temperatures ranging from 200 to 1200°C. However, the reaction rates for experiments conducted at 400°C (or lower) might be too slow to reach equilibrium conversion.…”
Section: Effect Of Reaction Temperature On Co 2 Yield and H 2 Generationmentioning
confidence: 99%